A novel and superior approach to diabetic management: utilization of a fuzzy-logic based system for precision insulin dosing in type 2 diabetes patients - Orni, Proma Roy (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.